PENGEMBANGAN SUMBER BELAJAR BERBASIS ETNOMATEMATIKA DENGAN MODEL PjBL PADA MATERI BANGUN RUANG PRISMA - KABU, THOMAS EDISON (Pendidikan Matematika UNIMOR, 2021)
ABSTRACT This research is the development of learning resource based on etnomatematics with the learning model of Project Based Learning (PjBL) on the building material of prism room. The purpose of this study is to determine the validity, practicality and effectiveness of etnomatematics-based learning resources. Learning resources are developed in the form of student books and student worksheets based on ethnomatematics construct the prism room. This research type is research and development by using Borg and Gall model. This research was conducted in Junior High School Christian 1 Soe with the culture used is the woven of West Amanuban society in the form of oko. The results of this study indicate that the source of learning developed valid with the average percentage obtained 92.5% and also practical use in learning mathematics with the average percentage of teacher response 86% and 95.5% student response. This learning resource is also effective based on post-test results indicating that the average test score in the experimental class is 76.96 far greater than the control class 61.70. The proportion of students' completeness in the experimental class is 83% complete classically. Based on the results of the calculation of normalized gain score known that the percentage increase in mathematics learning achievement class VIII Junior High School Christian 1 Soe after taught with the source of learning based on ethnomatematics with PjBL model is 60% are in the category of being.